Five-year overall survival of early- and late-onset colorectal cancer in Medellín, Colombia: a comparative study (2024)
ABSTRACT: Purpose: Early-onset colorectal cancer (CRC) (EOCRC, < 50 years) has distinct clinicopathological features from late-onset CRC (LOCRC, ≥ 50 years). However, evidence on survival outcomes is contradictory. We aimed to analyse the differences in 5-year overall survival (OS) between EOCRC and LOCRC. Methods: A retrospective cohort study was conducted during 2018-2022. Individuals aged ≥ 18 years diagnosed with CRC at two hospitals in Medellín, Colombia were included. Clinicopathological and survival data were retrieved from the medical records and a public government database. Patients were categorized into EOCRC and LOCRC groups. Five-year OS rates were calculated using the Kaplan-Meier method and prognostic factors for OS were identified through Cox regression models. Results: Among 1022 patients, 52.5% were female, and 13.5% (n = 138) had EOCRC. Patients with EOCRC showed higher 5-year OS rates than LOCRC patients (54% vs. 32%). Univariable analyses indicated a 37% lower risk of death for EOCRC compared to LOCRC (HR: 0.633, 95%CI: 0.476-0.840, p = 0.002). After multivariable analyses, advanced staging and higher tumour grading were prognostic factors for worse OS (HR: 2.127, 95% CI:1.405-3.220, p = 0.0001; and HR: 12.896, 95%CI: 6.310-26.355, p = 0.000; respectively), and being in the EOCRC group remained as a prognostic factor for higher OS (HR: 0.482, 95% CI: 0.336-0.690, p = 0.000). Conclusion: EOCRC is associated with significantly better 5-year OS rates and prognosis compared to LOCRC. Advanced stage and higher tumour grading are predictors of lower OS among all CRC patients. These findings highlight the importance of age-related risk stratification and personalized therapeutic approaches in CRC.